Impact of a 12-week aerobic exercise training program on anthropometric and metabolic parameters of a group of type 2 diabetes Cameroonian women aged ≥50 years - Dahjio, Yves; Noubiap, Jean Jacques N.; Azabji-Kenfack, Marcel; Essouma, Mickael; Loni, Gabriel Ekali; Ewane, Arnold Onana; Dehayem, Mesmin; Mvom, Angeline; Tadjore, Maurice Njock; Sobngwi, Eugene (Annals of Translational Medicine; Vol 4, No 19 (October 15, 2016): Annals of Translational Medicine, 2016)
Background: We examined whether aerobic exercise could have an impact on anthropometric and metabolic parameters of type 2 diabetes mellitus (T2DM) Cameroonian women aged ≥50 years. Methods: We enrolled 23 T2DM Cameroonian women aged ≥50 years regularly followed at the National Obesity Center of Yaounde, Cameroon, in a 12-week aerobic exercise program monitored by a pedometer. Exercise intensity was progressively set between 55% and 75% of maximum heart rate. We measured weight, body mass index (BMI), fat, lean mass, visceral fat, maximum oxygen uptake, glycaemia and insulin tolerance index at baseline, after six and twelve weeks. A mixed ANOVA model was used to evaluate changes of outcome measures over time. Results: Total body weight was significantly reduced after 12 weeks (P